2022
DOI: 10.3920/jiff2021.0190
|View full text |Cite
|
Sign up to set email alerts
|

Purification of novel polypeptides from bee pupae and their immunomodulatory activityin vivo andin vitro

Abstract: Edible insects have been proposed as an understudied food whose cultivation could be increased with global population growth. However, the bioactivators and bioactivities of bee pupae are poorly studied. In this paper, the active ingredients of bee pupa powder were analysed, and novel bee pupa polypeptides (BPP) were obtained through protein hydrolysis with alkaline protease. Two purified polypeptide components (BPP-21 and BPP-22) were isolated and purified on a diethylaminoethyl-sepharose fast flow column and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The cationic peptide fractions contained in the hydrolysate were able to inhibit LPS-induced inflammation in RAW 264.7 cells, although not exhibiting a dose-dependent behaviour in the range of the concentrations evaluated (0.5 to 3 µg mL −1 ). Similar to this, Chen et al 40 evaluated the potential of a bee pupa-derived peptide in RAW 264.7 cells, and according to the authors, this implied a promotion of IL-2, TNF-α and interferon gamma (IFN-γ) secretion, while also leading to the production of NO and increasing the phosphorylation of extracellular signal-regulated kinase (ERK) and p38, and modulating the expression of intranuclear transcription in the MAPK signalling pathway. In the context of the prevention of non-alcoholic fatty liver disease (NAFLD), the potential of Gryllus bimaculatus protein hydrolysates (obtained with Neutrase or Flavourzyme) in modulating hepatic lipid accumulation, inflammation, and endoplasmic reticulum stress in Hep G2 cells treated with palmitic acid was assessed.…”
Section: In Vitro and Cell-culture Assayssupporting
confidence: 72%
See 2 more Smart Citations
“…The cationic peptide fractions contained in the hydrolysate were able to inhibit LPS-induced inflammation in RAW 264.7 cells, although not exhibiting a dose-dependent behaviour in the range of the concentrations evaluated (0.5 to 3 µg mL −1 ). Similar to this, Chen et al 40 evaluated the potential of a bee pupa-derived peptide in RAW 264.7 cells, and according to the authors, this implied a promotion of IL-2, TNF-α and interferon gamma (IFN-γ) secretion, while also leading to the production of NO and increasing the phosphorylation of extracellular signal-regulated kinase (ERK) and p38, and modulating the expression of intranuclear transcription in the MAPK signalling pathway. In the context of the prevention of non-alcoholic fatty liver disease (NAFLD), the potential of Gryllus bimaculatus protein hydrolysates (obtained with Neutrase or Flavourzyme) in modulating hepatic lipid accumulation, inflammation, and endoplasmic reticulum stress in Hep G2 cells treated with palmitic acid was assessed.…”
Section: In Vitro and Cell-culture Assayssupporting
confidence: 72%
“…Recently, Chen et al 40 hydrolysed bee pupae with alkaline protease and were able to purify two peptides, and one of them was used to assess its immunomodulatory activity in vivo . In this regard, cyclophosphamide-treated immunosuppressed mice were exposed to the peptide, and this led to a significant increase in body weight growth rate, organ index, macrophage phagocytosis, delayed-type hypersensitivity reaction, and cytokine levels (IL-2, IFN-γ, IgA, IgG, and IgM).…”
Section: The Role Of Insect Peptides In Immunonutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…It enhanced the production of antibodies IgA, IgE, IgM, IL-2, INF-γ and elevated the phagocytic activity of macrophages in an immunosuppressied mouse model. It is suggested that BPP-22 exerts its immunomodulatory effects by elevating the phosphorylation of ERK and p38 and modulating the MAPK signaling pathway (Chen et al, 2022).…”
Section: Immunomodulatory Effects Of Edible Insect Extracts and Activ...mentioning
confidence: 99%
“…Insect derived lectins show anti-cancer immunomodulatory activity through M1 macrophage mediated phagocytosis (Cao et al, 2012). The capacity of insect peptides to modify the immune response against cancer cells has been shown in several researches (Sun et al, 2014;Chen et al, 2022;Yang K. et al, 2023). It has been seen that, some insect peptide fragments interact with immune cells, including DC, natural killer (NK) cells, and T lymphocytes, among others, and enhance their activity.…”
Section: Immunomodulatory Effects Of Edible Insect Extracts and Activ...mentioning
confidence: 99%